2018
DOI: 10.1111/rode.12409
|View full text |Cite
|
Sign up to set email alerts
|

Does energy‐related aid affect emissions? Evidence from a global dataset

Abstract: Donor countries have been using international aid in the field of energy for at least three decades. The stated objective of this policy is to reduce emissions and promote sustainable development in the global South. In spite of the widespread use of this policy tool, very little is known about its effect on emissions. In this paper we perform an empirical audit of the effectiveness of energy‐related aid in tackling CO2 and SO2 emissions. Using a global panel dataset covering 128 countries over the period 1971… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“…Noteworthy in this context, however, are the findings by Bhattacharyya et al. (2018), who could not find a systemic effect of energy‐related aid on emissions.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 88%
See 1 more Smart Citation
“…Noteworthy in this context, however, are the findings by Bhattacharyya et al. (2018), who could not find a systemic effect of energy‐related aid on emissions.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 88%
“…Other authors highlighted the usefulness of energy reform subsidies in these developing countries as well (e.g., Groot & Oostveen, 2019). Noteworthy in this context, however, are the findings by Bhattacharyya et al (2018), who could not find a systemic effect of energy-related aid on emissions.…”
Section: Developing Countriesmentioning
confidence: 93%
“…(Kretschmer et al 2013) examined the impact of total aid, industrial sector aid and energy sector aid on carbon emissions in developing countries and concluded that total aid and industrial sector aid had little impact on carbon emissions in recipient countries, while energy aid helped reduce energy intensity but not carbon emissions. (Bhattacharyya et al 2018) performed an empirical audit of the effectiveness of energy-related aid in tackling CO 2 emissions and showed that aid had no signi cant CO 2 emissions reduction effects. (Chung et al 2018) examined the effects of climate technology-related development nance on CO emissions of the recipient country and showed that climate technology-related development nance did not have a signi cant effect on CO emissions as a whole, but different types of technical aid had heterogeneous effects in different sectors.…”
Section: Climate Aid and Carbon Emissionsmentioning
confidence: 99%
“…Developing countries take their cues on climate policy from Europe and North America. There as well, patronage too often takes priority over emission reduction, and the various streams of climate funds are not without blemish (Mathy and Guivarch 2010, Michaelowa and Michaelowa 2007, Bhattacharyya, Intartaglia, and McKay 2016, Wara 2008. China is copying another European mistake.…”
Section: Progress In National Climate Policies?mentioning
confidence: 99%